Technology-Facilitated Sexual Violence Victimization: Results From an Online Survey of Australian Adults - Powell, Anastasia; Henry, Nicola (Journal of interpersonal violence, 2019)
Online forms of sexual harassment and abuse as experienced by adults represent an emerging yet under-researched set of behaviors, such that very few studies have sought to estimate the extent of the problem. This article presents the results of an online survey of 2,956 Australian adult (aged 18 to 54 years) experiences of technology-facilitated sexual violence (TFSV) victimization. The prevalence of TFSV was analyzed in relation to a 21-item scale developed in accordance with prior conceptual research identifying multiple dimensions of TFSV including digital sexual harassment, image-based sexual abuse, sexual aggression and/or coercion, and, gender and/or sexuality-based harassment (including virtual sexual violence). Results revealed significant differences in lifetime TFSV victimization for younger (18-24) and non-heterosexual identifying adults. Lifetime TFSV victimization for men and women was not significantly different, though women were more likely to report sexual harassment victimization and men were more likely to report victimization through the distribution of non-consensual images, as well as gender and/or sexuality-based harassment. The authors conclude that although women and men report experiencing similar overall prevalence of TFSV victimization, the nature and impacts of those experiences differ in particular gendered ways that reflect broader patterns in both gender relations and “offline” sexual harassment.